Are Physical Activity Interventions Effective in Improving Health-Related Quality of Life in Children and Adolescents? a Systematic Review and Meta-Analysis - Garcia-Hermoso, A (SAGE Publications Inc., 2024)
Context: Physical activity (PA) interventions improve well-being and positive mental health in children and adolescents, but the results of previous systematic reviews included participants with chronic medical conditions and did not accurately assess the multidimensional nature of health-related quality of life (HRQoL). Objective: The aims of this meta-analysis were to (1) evaluate the effects of PA interventions on several domains of HRQoL in healthy <18-year-olds and (2) examine the effectiveness of interventions on HRQoL according to whether they were successful in increasing PA, the type of intervention delivered, and the duration of the intervention. Data Sources: PubMed (Medline), EMBASE, the Cochrane Library, SCIELO, SPORTDiscus, and PEDro databases were systematically searched from inception to September 30, 2022. Study Selection: Experimental studies that examined the effectiveness of PA interventions on HRQoL participants aged <18 years. Study Design: Systematic review with meta-analysis and meta-regression. Level of Evidence: Level 1. Methods: Random-effects models were used to calculate pooled effect size (ES) for total HRQoL score and its dimensions. Subgroup analyses were conducted to examine the effect of PA program characteristics. Results: A total of 17 studies were included. Pooled ES (95% CI) estimations were as follows: 0.179 (0.045, 0.002) for total HRQoL score, 0.192 (0.077, 0.306) for physical well-being, 0.158 (0.080, 0.237) for psychological well-being, 0.118 (0.044, 0.192) for autonomy and parent relation, 0.135 (0.043, 0.227) for social support and peers, and 0.129 (-0.013, 0.270) for school environment. Subgroup analyses suggested there were no differences in the effectiveness of the interventions by category of PA increase or by type and duration of intervention. Conclusion: Exercise interventions are an effective strategy for improving overall HRQoL and its most significant domains in children and adolescents. © 2023 The Author(s).